The crown. The complete third season [videorecording (DVD)]. - Colman, Olivia; Menzies, Tobias, 1974-; Bonham Carter, Helena, 1966- (Sony Pictures Home Entertainment, 2020)
During the period between 1964 and 1977: the royal family mourns the passing of Winston Churchill; the United Kingdom ushers in a new prime minister, the Labour Party's Harold Wilson whom Prince Philip and Queen Elizabeth hear might be a Soviet spy; survives the Aberfan disaster; observes the Apollo 11 moon landing; and plans for the Investiture of Prince Charles. While Princess Margaret and Lord Snowdon visit the USA, the queen, at the bidding of Harold Wilson, asks them to make a side trip to Washington, D.C. to ask President Johnson for financial assistance for the United Kingdom.